Correspondence assertions for process synchronization in concurrent communications - Bonelli, Eduardo (2004)
High-level specification of patterns of communications such as protocols can be modeled elegantly by means of session types. However, a number of examples suggest that session types fall short when finer precision on protocol specification is required. In order to increase the expressiveness of session types we appeal to the theory of correspondence assertions. The resulting type discipline augments the types of long term channels with effects and thus yields types which may depend on messages read or written earlier within the same session. We prove that evaluation preserves typability and that well-typed processes are safe. Also, we illustrate how the resulting theory allows us to address the shortcomings present in the pure theory of session types.